Pharmacists' social authority to transform community pharmacy practice - Timothy McPherson; Patrick Fontane (INNOVATIONS in Pharmacy, 2011)
Leaders in the profession of pharmacy have articulated a vision of pharmacists as providers of patient-centered care (PCC) services and the Doctor of Pharmacy was established as the required practice degree to achieve this vision. Pharmacist-provided PCC services have been shown to reduce medication costs and improve patient compliance with therapies. While community pharmacists are capable of, and are ideally placed for, providing PCC services, in fact they devote most of their time to prescription dispensing rather than direct patient care. As professionals, community pharmacists are charged with protecting society by providing expert services to help consumers manage risks associated with drug therapies. Historically pharmacists fulfilled this responsibility by accurately dispensing prescription medications, verifying doses, and allergy checking. This limited view of pharmacy practice is insufficient in light of the modern view of pharmacists as providers of PCC. The consumers' view of community pharmacy as a profession represents a barrier to transforming the basis of community pharmacy from product distribution to providing PCC services. Community pharmacists are conferred with social authority to dictate the manner in which their professional services are provided. Pharmacists can therefore facilitate the transition to PCC as the primary function of community pharmacy by exercising their social authority to engage consumers in their roles in the new patient-pharmacist relationship. Each pharmacist must decide to provide PCC services. Suggestions for initiating PCC services in community pharmacy are offered.